2012
DOI: 10.1186/1471-2431-12-121
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric first aid knowledge and attitudes among staff in the preschools of Shanghai, China

Abstract: BackgroundUnintentional injury remains the leading cause of morbidity and mortality among children worldwide. The aims of this study were to assess a baseline level of first aid knowledge and overall attitudes regarding first aid among staff members in Shanghai preschools.MethodsA cross-sectional study was carried out among the staff members at selected preschools. A stratified random sampling method was first used to identify suitable subjects. Data were obtained using a multiple-choice questionnaire. A stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
3
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 24 publications
7
51
3
6
Order By: Relevance
“…10 In study conducted by Li et al, in 2012 in China had similar result among the personals that took care of children. 11 However, Deepak and Nayak in 2012 studied the KAP on first aid practices among selfhelp group in India suggest that 62% had good knowledge and 38% had average knowledge which is in contrast of our study findings. 12 It was found by Priyangika and Hettiarachchi in Sri Lanka in 2015 that more than 50% of students knew basic first aid for burn and fracture.…”
Section: Discussioncontrasting
confidence: 57%
“…10 In study conducted by Li et al, in 2012 in China had similar result among the personals that took care of children. 11 However, Deepak and Nayak in 2012 studied the KAP on first aid practices among selfhelp group in India suggest that 62% had good knowledge and 38% had average knowledge which is in contrast of our study findings. 12 It was found by Priyangika and Hettiarachchi in Sri Lanka in 2015 that more than 50% of students knew basic first aid for burn and fracture.…”
Section: Discussioncontrasting
confidence: 57%
“…In the study conducted in Ankara, it was found that only 16.7% of the pre-school educators knew the necessary first-aid practice in cases of insect bites (12). In a study conducted in China, it was found that 41.7% of the pre-school teachers knew that the wounded area should be washed under running water in case of injury (19). The different rates of correct answers found may be related with the differences in the levels of knowledge of the participants or the differences in the ways of establishing the questions and lack of use of a standard measurement method.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] In contrast, several studies done in Asia have reported awareness, perception and practices of first aid among teachers to be poor. 3,[7][8][9] This study was undertaken to assess the awareness, attitudes and practices of first aid among school teachers and to assess the first aid facilities in schools in Mangalore, a coastal city in south India.…”
Section: What This Study Addsmentioning
confidence: 99%